"Hay que seguir en la lucha": An FQHC's Community Health Action Approach to Promoting Latinx Immigrants' Individual and Community Resilience. Issue 3 (1st October 2020) - Yamanis, Thespina (Nina) J.; Morrissey, Taryn; Bochey, Lisa; Cañas, Natalia; Sol, Catalina
Abstract: Latinx immigrants have poorer access to health care, compared to non-Latinx Whites. Federally-Qualified Health Centers (FQHCs) provide clinical and community programing to address their clients' health needs. One mechanism by which FQHC's may strengthen Latinx immigrant well-being is by promoting their individual and community resilience. We partnered with La Clínica del Pueblo (La Clínica), an FQHC serving Latinx immigrants in Washington, DC and Prince George's County, Maryland. We conducted in-depth interviews in Spanish with 30 La Clínica clients to explore the daily adversities they faced, how they coped, and how La Clínica helped them cope. We conducted thematic analysis using Dedoose software. All participants were from Central America; 37% were undocumented. Participants were 18–78 years old, 70% cis-females, 23% cis-males (10% gay men), and 7% transgender. 57% reported a serious health issue, including diabetes. Participants identified three main adversities: immigration legal status, language, and isolation/depression. Residents of Prince George's, compared to DC, as well as sexual/gender minorities, reported more barriers to accessing health care. Sources of individual resilience for participants included fighting to improve their children's lives, relying on supportive networks, and using La Clínica as a safety net to overcome health access barriers. Sources of community resilience included La Clínica's safe spaces, support groups, referrals to outside legal service providers, and health promoter training. Latinx immigrants face multiple daily adversities, but we find evidence that La Clínica's community health action approach promotes their resilience. We offer a conceptual model for how FQHCs can foster resilience and strengthen immigrant health.